Analisis Pendapatan Agroindustri Tahu di Desa Nogosari Kecamatan Rambipuji Kabupaten Jember - Purwandhini, Ari Septianingtyas; Utami, Nurul Emilia Wahyu (KUBIS, 2021)
Tofu has become a food tradition for Indonesian people and is traded in various variations, shapes, sizes, and names. However, many entrepreneurs do not keep their bookkeeping properly and regularly, making it difficult to manage the finances of the business they run. Based on this, this research aims to analyze income and cost efficiency. Data collection was carried out at the tofu agro-industry in Nogosari Village, Rambipuji District, Jember Regency. The choice of place was carried out deliberately (Purposive Method), with the methods used being descriptive and analytical. The sampling method in this research used the Total Sampling method, namely 13 respondents. The data analysis used is income analysis and RC Ratio analysis. Based on the results of the research and discussion, the following conclusions can be drawn: 1. TR > TC value, so it can be said that the income of the tofu agro-industry in Nogosari Village is profitable. The use of tofu agro-industry production costs in Nogosari Village, Rambipuji District, Jember Regency is efficient. This is indicated by an RCR value ≥ 1, namely 1.49.